Burning down the house: IRF7 makes the difference for microglia. (13th November 2014) - Hagemeyer, Nora; Prinz, Marco
<x xml:space="preserve">Abstract</x> The endogenous microenvironment of the brain is an essential watchdog to guard over myeloid cell function during diseases. Limiting inflammatory reactions of activated microglia and blood‐derived monocytes is a key prerequisite for the resolution of tissue insults. So far, however, it was unknown why monocytes but not microglia are able to shift to an anti‐inflammatory state during inflammation. In this issue of The EMBO Journal, Cohen and colleagues identified the molecular switch underlying this fundamental functional change. The authors found that the transforming growth factor‐β1 (TGFβ1) prevents activated microglia to switch to an anti‐inflammatory state by regulating the expression of Irf7.